P458 Long-term outcome of Crohn's disease complicated by upper gastrointestinal stricture: A GETAID cohort study. (16th January 2018) - Lambin, T; Amiot, A; Gornet, J M; Seksik, P; Laharie, D; Louis, E; Giletta, C; Filippi, J; Fumery, M; Cadiot, G; Pineton de Chambrun, G; Nahon, S; et al.
Abstract: Background: The aim of the present study was to evaluate outcomes and treatments efficacy in Crohn's disease (CD) patients with severe strictures of the upper gastrointestinal (UGI) tract. Methods: We performed a retrospective study in 18 centres from the GETAID, including all CD patients with an non-passable UGI stricture on upper endoscopy. The primary outcome was the surgery-free survival from diagnosis of stricture. Short-and long-term clinical efficacy (defined as a relief of obstructive symptoms) and endoscopic efficacy (defined as ability to pass the scope beyond the stricture) of medical, endoscopic and surgical treatments and identification of predictors of surgery were also evaluated. Results: From 1988 to August 2017, 43 CD patients with a non-passable stricture on upper endoscopy were included: 40% were female and 9% were active smoker. Median disease duration from CD to stricture diagnosis was 7 (IQR: 0–13.5) years. Location of stenosis was: 4 (9%) oesophagus, 6 (14%) stomach, 28 (65%) duodenum, 3 (7%) proximal jejunum, and 2 (5%) evolving both pylorus and duodenum. Forty (93%) patients had primary stricture and 3 (7%) anastomotic stricture. Median follow-up from stricture diagnosis to last news was 5 (IQR: 2–10.5) years. Surgical-free survival was 80%, 75%, 61% and 49% at 1, 3, 5, and 7 years, respectively. Medical treatment of the stricture consisted in: immunosuppressant in 27 cases with as short-term clinical efficacy in 13 (48%) cases and endoscopic efficacy in 3 (11%) cases; anti-TNF therapy in 28 cases with a short-term clinical efficacy in 17 (60%) cases and endoscopic efficacy in 7 (25%). Thirty-nine endoscopic procedures (30 dilations, 7 stents, 2 gastroenteroanastomosis) were realised with a short-term clinical efficacy in 31 (79%) cases and endoscopic efficacy in 23 (59%) cases; a complication occurred in four (10%) cases (three perforations and one haemorrhage). At the end of follow-up, 21 (49%) patients were not operated. Twenty-five surgeries were performed with a short-term clinical efficacy in 21 cases (84%) for a median time of 61 (IQR: 12–127) months. A complication occurred in eight (32%) cases (2 perforations, 1 death, 1 pulmonary embolism, 1 anastomotic stricture, 1 haematoma, 1 haemorrhage, 1 gastroenteroanastomosis dysfunction). In multivariate analysis, risk of surgery was greater for active smokers ( p = 0.04), and lower for patients receiving anti-TNF treatment at stricture diagnosis ( p = 0.02). Conclusions: Surgery is often necessary in CD patients with severe stricture of the UGI, especially in active smokers. Medical and endoscopic treatments are efficient in the majority of the patients at short-term and allow avoiding surgery in almost half the patients at long term.